Conjugated polyelectrolyte-based ternary exciton funnels via liposome scaffolds. Issue 4 (1st February 2022) - Palmer, Jack; Segura, Carmen J.; Matsushima, Levi; Abrams, Benjamin; Lee, Hsiau-Wei; Ayzner, Alexander L.
Abstract : We used a vesicle scaffold to form a ternary, quasi-panchromatic funnel for electronic excited states oriented from the outer surface towards the membrane. We did so via electronic energy transfer (EET) from two conjugated polyelectrolytes to a phthalocyanine. Abstract : There is great interest in developing inexpensive, molecular light-harvesting systems capable of efficiently converting photon energy to chemical potential energy. It is highly desirable to do so using self-assembly and in a manner that supports environmentally benign processing. A critical consideration in any such assembly is the ability to absorb a substantial fraction of the solar emission spectrum and to be able to efficiently move excited states through the space to a functional interface. We have previously shown that aqueous inter-conjugated polyelectrolyte (CPE) complexes can act as ultrafast and efficient energy-transfer antennae. Here we demonstrate formation of a hierarchically assembled, aqueous system based on an inter-CPE exciton donor/acceptor network and a lipid vesicle scaffold. Using a model small-molecule organic semiconductor embedded in the vesicle membrane, we form a ternary exciton funnel that is oriented towards the membrane interior. We show that, although energy transfer is efficient, the assembly morphology depends sensitively on preparation conditions and relative ionic stoichiometry. We propose several approaches towards stabilizing such aqueous assemblies. This work highlights a path to formation of an aqueous, panchromatic light-harvesting system, whose functional complexity can be systematically increased with modularity.